Real-world study of rurioctocog alfa pegol and emicizumab in US clinical practice among patients with hemophilia A. Issue 10 (3rd October 2022) - Sun, Shawn X.; Frick, Andrew; Balasa, Vinod; Roberts, Jonathan C.
ABSTRACT: Background: FVIII replacement is standard treatment for hemophilia A without inhibitors, but non-factor therapies, such as emicizumab, are changing the treatment landscape. We explore the ramifications of switching treatment. Methods: Pharmacy database data (July 2017–May 2020) from patients with hemophilia A without inhibitors who switched to rurioctocog alfa pegol or emicizumab prophylaxis after ≥6 months' prophylaxis with another FVIII product were analyzed for total mean weekly consumption, dosing frequency, product wastage, and ABR. Results: Post-switch mean weekly consumption of prophylactic rurioctocog alfa pegol and emicizumab were 6224 IU/kg and 109 mg, respectively. Dosing schedules for emicizumab were primarily weekly (48.2%) and every 2 weeks (40.0%). Most patients in the rurioctocog alfa pegol cohort received treatment twice-weekly (83.3%). Mean product wastage of emicizumab (8.4%) was significantly higher versus rurioctocog alfa pegol (−0.3%; P < 0.001). Mean annualized emicizumab and rurioctocog alfa pegol wastage during prophylaxis was 330.82 mg and −974.80 IU, respectively. ABR change was not significantly different ( P = 0.527) for patients switching to emicizumab (−1.05) or rurioctocog alfa pegol (−1.53). Conclusions: Bleed rates were similar for patients receiving prophylaxis with emicizumab or rurioctocog alfa pegol after switching from prophylaxis with another FVIII. However, wastage associated with dispensing inaccuracies was greater with emicizumab.